Analisis Pencatatan dan Pelaporan Wakaf dalam Meningkatkan Kesejahteraan Masyarakat di Kecamatan Sibulue Kabupaten Bone - Sakinah, Nurul Yasin; Susi, Susi; Hasbi, Hartas (Universitas Serambi Mekkah, 2024)
The aim of this research is to evaluate the waqf recording and reporting system in Sibulue District, Bone Regency, and its impact on improving community welfare. The main focus of the research includes the process of recording, reporting, as well as obstacles that arise during waqf management. Descriptive qualitative methods were used, with direct observation, through interviews and documentation studies as data collection methods. The research informants consisted of the Office of Religious Affairs (KUA), namely the head of the KUA Kec. Sbulue. The research results revealed that of a total of 127 waqf land locations, only 22% had official certification. Barriers identified include the lack of an adequate filing system, low public understanding of waqf administration, and weak synergy between related agencies. This research recommends developing a digital-based recording system, increasing public education, waqf land certification, and more optimal supervision. The implementation of better waqf management is expected to have a positive impact in the form of more significant social and economic benefits for society.